Влияние метаболитов Bacillus sp. из многолетнемерзлых пород на выживаемость эмбрионов рыб - Еnoktaeva,O. V.; Kalyonova, L. F.; Subbotin, A. M.; Еноктаева, О. В.; Калёнова, Л. Ф.; Субботин, А. М. (Издательство Тюменского государственного университета, 2014)
Anthropogenic impact on the natural water leads to a decrease in the natural population of hydrobionts. Scientific reference and own data are considered with respect to the positive impact of the biological factors on the embryogenesis of fish. Seen as a biological method, in this paper the effect of metabolites Bacillus sp. strain MG8 are studied. The microorganisms were isolated from samples of permafrost in Central Yakutia. The metabolites were added to sexual products and embryos of the loach Misgurnus fossilis L., which developed from the eggs of poor quality. The following criteria of development, characterizing early ontogenesis of fish, are considered: the quality of eggs, the ability to fertilize ovulated eggs and their normal development, the survival of embryos, the survival of prelarvae when they come out of their shells. During the research the concentration of metabolites, which increases the survival of fish embryos, developing from eggs of poor quality, was evaluated. Three methods of adding metabolites to sexual products were examined, and it is concluded that the most effective method is to add them to sperm with subsequent addition during the early ontogenesis. Антропогенная нагрузка на естественные водоемы приводит к сокращению численности природных популяций гидробионтов. Рассматриваются литературные и собственные данные, свидетельствующие о положительном воздействии факторов биологической природы на эмбриогенез рыб. В качестве биологического метода в данной работе изучается действие метаболитов Bacillus sp. штамма МG8, выделенных из образцов многолетнемерзлых пород Центральной Якутии при добавлении их к половым продуктам и к эмбрионам вьюна Misgurnus fossilis L., развивающихся из икры низкого качества. Рассмотрены следующие критерии развития, характеризующие ранний онтогенез рыб: качество икры, способность овулировавших яйцеклеток к оплодотворению и нормальному развитию, выживаемость эмбрионов, выживаемость предличинок в момент выхода их из оболочек. В ходе работы определена концентрация метаболитов, повышающая выживаемость эмбрионов рыб. Проанализированы три метода добавления метаболитов к половым продуктам, наиболее эффективным из которых является добавление их к спермиям и в период эмбрионального развития.